DEL-1, as an anti-neutrophil transepithelial migration molecule, inhibits airway neutrophilic inflammation in asthma - Jia,M; Fu,H; Jiang,X; Wang,L; Xu,J; Barnes,PJ; Adcock,IM; Liu,Y; He,S; Zhang,F; Yao,L; Sun,P; et al. (Allergy, 2024)
BackgroundNeutrophil migration into the airways is a key process in neutrophilic asthma. Developmental endothelial locus-1 (DEL-1), an extracellular matrix protein, is a neutrophil adhesion inhibitor that attenuates neutrophilic inflammation.MethodsLevels of DEL-1 were measured in exhaled breath condensate (EBC) and serum in asthma patients by ELISA. DEL-1 modulation of neutrophil adhesion and transepithelial migration was examined in a co-culture model in vitro. The effects of DEL-1-adenoviral vector-mediated overexpression on ovalbumin/lipopolysaccharide (OVA/LPS)-induced neutrophilic asthma were studied in mice in vivo.ResultsDEL-1 was primarily expressed in human bronchial epithelial cells and was decreased in asthma patients. Serum DEL-1 concentrations were reduced in patients with severe asthma compared with normal subjects (567.1 ± 75.3 vs. 276.8 ± 29.36 pg/mL, p < .001) and were negatively correlated to blood neutrophils (r = −0.2881, p = .0384) and neutrophil-to-lymphocyte ratio (NLR) (r = −0.5469, p < .0001). DEL-1 concentrations in the EBC of severe asthmatic patients (113.2 ± 8.09 pg/mL) were also lower than normal subjects (193.0 ± 7.61 pg/mL, p < .001) and were positively correlated with the asthma control test (ACT) score (r = 0.3678, p = .0035) and negatively related to EBC IL-17 (r = −0.3756, p = .0131), myeloperoxidase (MPO) (r = −0.5967, p = .0055), and neutrophil elastase (NE) (r = −0.5488, p = .0009) expression in asthma patients. Neutrophil adhesion and transepithelial migration in asthma patients were associated with LFA-1 binding to ICAM-1 and inhibited by DEL-1. DEL-1 mRNA and protein expression in human bro